Operations management : strategy and analysis - Krajewski, Lee J.; Ritzman, Larry P. (Reading, Mass. : Addison-Wesley Pub. Co., 1993)
For the introductory Operations Management course, at both the undergraduate and graduate level. This classic text presents strategic and managerial issues in order to emphasize that the decisions made by operations managers should be consistent with a corporate strategy shared by managers in all functional areas. It presents the operations tools and techniques for solving problems in the context of achieving a firm's overall goals and strategies.
Includes bibliographical references and index.
oif 18/03/15
Loan
Keywords: Production management; Industrial management; Strategic planning